A Few Conditions for a C*-Algebra to Be Commutative - Lajos Molnár (Abstract and Applied Analysis)
We present a few characterizations of the commutativity of C*-algebras in terms of particular algebraic properties of power functions, the logarithmic and exponential functions, and the sine and cosine functions.